HR‐LC‐ESI‐Orbitrap‐MS based metabolite profiling of Prunus dulcis Mill. (Italian cultivars Toritto and Avola) husks and evaluation of antioxidant activity. Issue 4 (14th February 2019) - Bottone, Alfredo; Masullo, Milena; Montoro, Paola; Pizza, Cosimo; Piacente, Sonia
Abstract: Introduction: Prunus dulcis Mill. is a plant cultivated for the production of its edible seeds, known as sweet almonds. In the last decades almond demand has highly increased due to their wide use in the industrial manufacturing of almond‐based foods; this has led to a huge production of waste materials, mainly corresponding to shells and husks. Objective: To achieve a deeper understanding of the chemical composition of almond husks with the aim of exploring these byproducts as a source of bioactives to be used in nutraceutical and cosmetic formulations. Methods: Methanol, ethanol and ethanol–water extracts of the almond husks were analysed by high‐resolution liquid chromatography electrospray ionisation Orbitrap mass spectrometry (HR‐LC‐ESI‐Orbitrap‐MS) in negative ion mode. Tandem mass spectrometry (MS/MS) data were acquired by using the Data‐Dependent Scan experiment, allowing the precursor ion to be selected as the most intense peak during LC‐MS analyses. Nuclear magnetic resonance (NMR) experiments were performed on a Bruker DRX‐600 spectrometer. Folin–Ciocalteu, DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) and TEAC (Trolox equivalent antioxidant capacity) assays were employed to determine the total phenolic content and the radical scavenging activity of the extracts. Results: The LC‐MS/MS analysis of the methanol extract guided the isolation of phloroglucinol derivatives, flavonoids and terpenes. Eco‐friendly extraction methods showed to be selective in extracting flavonoids while the comparison of the LC‐MS profiles of the Italian cultivars Toritto and Avola showed significant differences, confirming how different growing conditions may influence the metabolome of a plant species. Conclusion: This study led to a deeper insight into the chemical constituents of almond husks and showed how the eco‐friendly extraction resulted in an effective method to obtain extracts rich in antioxidant sources. Abstract : The methanol extract of the husks of Prunus dulcis, cultivar Toritto, one of the most appreciated in Italy, was investigated by HR‐LC‐ESI‐Orbitrap‐MS analysis. The LC‐MS profile guided the isolation of compounds occurring in the methanol extract, of which the structures were elucidated by 1D‐ and 2D‐NMR experiments. The LC‐MS profile was compared with the LC‐MS profiles of ethanol and ethanol:water extracts of cultivar Toritto and other Italian cultivars represented by the Sicilian Avola, namely Fascionello, Pizzuta and Romana.